Recensione di Penna, Sandro. Within the Sweet Noise of Life. Seagull Books, 2021 (ENTHYMEMA, 2022)
Review of Within the Sweet Noise of Life, by Sandro Penna (Seagull Books 2021).
Keywords: Italian Poetry; Sandro Penna; English Translations; World Literature